OPTIMALISASI LAMA PEMAPARAN LASERPUNKTUR PADA TITIK REPRODUKSI TERHADAP PENINGKATAN NILAI HEPATO SOMATIC INDEX (HSI) DAN GONADO SOMATIC INDEX (GSI) IKAN GABUS (Channa striata) - Pungky Slamet Wisnu Kusuma (FMIPA : Universitas PGRI Adi Buana, 2017)
Snakefish fishing continuously can reduce the number of mature stem gonad great sizenya increasingly few in number in nature will certainly affect the reduction in seed production in the waters and may even become extinct. Efforts should be made restoking with laserpuncture technology. Laserpuncture technology has been shown to accelerate the maturation of the gonads in tilapia, catfish, shrimp, crab, but has never been tried on the snakefish brood (Channa striata). The purpose of this study to obtain optimum exposure time laserpuncture at the acupoint of reproduction to increase the value of HSI and GSI snakefish (Channa striata) male parent in order to get ready for spawning. Research experiments using CRD with 5 treatments and repeated 3 times. To get the value of HSI and GSI by weighing the weight, liver weight and gonadnya. The sample used in this study snakefish brood 1 year old male with a weight range from 1100-1400 grams have never spawn. HSI and GSI value analysis using ANOVA Gen Stat program version 15. The results showed exposure at the acupoint of reproduction laserpuncture significant effect (P <0.05) increase in the value of HSI and GSI. Laserpuncture exposure time at the acupoint of reproduction for 4 seconds proved to be optimal to increase the value of HSI and GSI parent catfish than in controls. Keywords: Laserpuncture, the value of HSI and GSI snakefish